HIV Sero-Prevalence among Infants Attending Immunization Centers in Calabar Metropolis, Cross River State, Southern, Nigeria - Ifeoma, Venn J.; Sunday, Ochigbo O.; Maxwell, Anah U.; Asindi, Asindi A. (International Journal of Child Health and Nutrition, 2016)
Introduction: Pediatric Human Immunodeficiency Virus (HIV) infection accounts for over 2.3% of all pediatric infections. Many HIV-infected infants are not identified until they develop symptoms and present with illness at health facilities. However, the six weeks immunization visit provides an opportunity for HIV-infected mothers and their exposed infants to be identified before symptoms occur. This study was therefore conducted to determine the HIV status of infants attending immunization clinics in Calabar with a view to enrolling them into treatment. Subjects and Method: This cross sectional descriptive study was conducted in two Local Government Areas of Calabar consisting 22 selected immunization centers. Using the multistage sampling method, 330 infants were screened. Ethical clearance was obtained from the supervising Ministry of Health. Rapid test was conducted, reactive specimens had Deoxyribonucleic Acid Polymerase Chain Reaction (DNA PCR) done using Dried Blood Spots (DBS). Results: A total of 330 infants aged 6 to 14 weeks were recruited, 173 (52.4%) were males while 157(47.6%) were females giving male to female ratio of 1.1:1. Mean age of the infants was 9.20 ± 3.1 weeks. Twenty four (24) tested positive for HIV antibodies, after HIV DNA PCR test, 14(4.2%) infants were infected. Antenatal care registration (ANC) and maternal ANC HIV status were statistically significant P=0.03 and P= 0.02 respectively. Conclusion: HIV exposed and infected infants are still been missed and only diagnosed later in life. Therefore, maternal HIV status determination and early diagnosis at immunization centers is recommended to bridge the Prevention of Mother To child Transmission (PMTCT) gap.